Corelation Between Worm Infection and Anemia in Pregnant Women at Sikumana Health Center, Kupang - Mindarsih, Theresia; Hurek, Rosina Kardina Kidi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
One of the causes of anemia is worm infection. Data from baseline health research showed an increase in the prevalence of anemia from 2013 by 37.1% to 48.9% in 2018. The research objective was to determine the correlation between deworming and the genesis of anemia on pregnant women at the public health center of Sikumana in Kupang City 2020. This research is analytical in nature and quantitative approach. Cross-sectional research design. The data used are primary data with instruments in the form of questionnaires and sampling in the form of feces and blood for laboratory examination. The data analysis technique was using the Chi-square test using SPSS 20. The results of this research showed that most pregnant women did not have worm infections, 104 respondents and 68 respondents had anemia. The results of the chi-square test found that there was no correlation between worms and anemia on pregnant women as indicated by a p-value of 0.673 (less than 0.05). These results are supported by personal hygiene data which shows that most pregnant women have performed personal hygiene properly and correctly, starting from the habit of using a healthy latrine, bathing regularly, washing hands before and after eating, washing feet, using footwear, and diligently cutting nails. as well as cleaning the environment. Therefore, it is expected that there will be further research and health promotion activities to increase knowledge and maintain a clean and healthy lifestyle. Abstrak: Salah satu penyebab anemia adalah infeksi kecacingan. Data Riskesdas yang dilakukan menunjukan terjadi peningkatan prevalensi anemia dari tahun 2013 sebesar 37,1% menjadi 48,9% ditahun 2018. Penelitian ini bertujuan mengetahui hubungan kecacingan dengan kejadian anemia pada ibu hamil di Puskesmas Sikumana Kota Kupang tahun 2020. Penelitian ini bersifat analitik dengan pendekatan kuantitatif. Desain penelitian cross sectional. Data yang digunakan adalah data primer dengan instrumen berupa kuesioner dan pengambilan sampel berupa faeces dan darah untuk dilakukan pemeriksaan laboratorium. Teknik analisa data dengan uji chisquare menggunakan SPSS 20. Hasil penelitian ini menunjukan sebagian besar ibu hamil tidak mengalami infeksi kecacingan 104 responden dan sebanyak 68 responden mengalami anemia. Hasil uji chi square ditemukan tidak ada hubungan antara kecacingan dengan kejadian anemia pada ibu hamil yang ditunjukan dengan nilai p value 0.673 (kurang dari 0.05). Hasil ini didukung dengan data personal hygiene yang menunjukan sebagian besar ibu hamil telah melakukan personal hygiene dengan baik dan benar mulai dari kebiasaan menggunakan jamban yang sehat, mandi teratur, mencuci tangan sebelum dan sesudah makan, mencuci kaki, menggunakan alas kaki, dan rajin memotong kuku serta membersihkan lingkungan. Oleh karena itu, diharapkan adanya penelitian lanjutan dan kegiatan promosi kesehatan untuk meningkatkan pengetahuan dan mempertahankan perilaku hidup bersih dan sehat.